ANALISIS PERBANDINGAN TINGKAT PERMINTAAN OBLIGASI KONVENSIONAL DAN SUKUK (OBLIGASI SYARIAH) - Jubaidi Jubaidi (LPPM University 17 Agustus 1945 Samarinda, 2020)
ABSTRACTSukuk is one instrument that adds to the diversity of Islamic products in the capital market. The existence of sukuk increasingly competes with the number of conventional bonds that have long been circulating in the community. Therefore, this study aims to describe the comparison of the level of demand between conventional bonds and sukuk in 2014-2018. The method used in this study is a quantitative method with a type of comparative research, where this study takes data in the form of monthly time series data in a span of 5 years starting from 2014-2018. Data collected in the form of the number of bonds and corporate sukuk in circulation. The analytical tool used in this study was the t-test which in the subsequent process used SPSS assistance. The results of this study indicate that there is a comparison that shows the difference between the level of demand for bonds and sukuk.